Influence of temperature and different culture media on growth of fusarium udum (Butler), causal organism of wilt of pigeonpea - Desai, Udaysingh; Andoji, Yogesh; Kamble, Shivaji (International Journal of Biological Research, 2016)
The conditions suitable for growth of Fusarium udum causing wilt of Pigeon pea were analysed. Pigeon pea seed agar medium and Czapek Dox Agar medium was found to be most suitable growth medium for mycelial growth and sporulation of Fusarium udum. The optimum temperature for growth of Fusarium udum was found to be 28Â±2Â°C.